Single-Layer Wideband CP CPW-Fed Antenna based on Staircase-Shape Metasurface - Nathapat Supreeyatitikul; Prayoot Akkaraekthalin; Chuwong Phongcharoenpanich (My University, 2021)
This research proposed a single-layer wideband circularly polarized (CP) coplanar waveguide (CPW)-fed antenna based on staircase-shaped metasurface (MTS) for C-band applications. The proposed CPW-fed antenna was a single-layer, which consisted of 4 × 4 periodic staircase-shaped MTS on the upper layer, a CPW feed, and a rectangular slot ground plane on the lower layer. A linearly polarized (LP) wave was generated by a CPW with a slot ground plane and converted to a circularly polarized wave by staircase-shaped MTS elements. The dimensions of the proposed antenna were 0.54λ × 0.54λ × 0.04λ at the lowest operating frequency. The simulated results of impedance bandwidth (IBW) and axial ratio (ARBW) at the center frequency of 5.2 GHz were 67.3% (4.1 – 7.6 GHz) and 15.9% (4.8 – 5.7 GHz), respectively. The maximum gain was 5.6 dBi at 5.3 GHz. The radiation patterns of the proposed CPW-fed antenna based on staircase-shaped MTS were right-hand circular polarization (RHCP) characteristic radiation at the operating frequency.
Keywords: Antenna Design and Analysis; Advanced Antenna and Metasurface Technologies; Microwave Engineering and Waveguides